Developing the competence to use chemistry lingo for student highschool through organizing project learning - Trịnh Lê Hồng Phương (Journal of Technical Education Science, 2015)
Organizing project learning in high school is one of the many viable methods to help the development of the competence to use chemistry lingo (TCTUCL) proceed faster, more easily and more efficiently. This report introduces the process of organizing project learning toward the development TCTUCL for student high school based on the research results about: the concept, the structure, the manifestations of TCTUCL and in compliance with the 6 principles and 10 steps of the competence developing process.